Synthesis and Characterization of Alumina Nanofiber Reinforced Poly Ether Ether Ketone (PEEK) - Mohd Ridzuan, Nordin; Tg Mahizatulazwa, Tg Kamaruddin; Yong, Liew Kong (Universiti Teknologi Malaysia, 2011)
The effects of reinforcing Poly ether etherketone (PEEK) with alumina nanofiber have been studied. The nano-composites were prepared by first dispersing the fibre in solvent and then undertaking the synthesis of PEEK. Nanocomposite materials with 1wt.%, 2.5wt.% and 5wt.% of alumina nanofiber have been prepared successfully by dispersing the alumina nanofiber in Sulfolane as solvent and upon sonication for 30 minutes. Transmission electron microscopy and scanning electron micrographs indicated excellent dispersion and interactions between PEEK matrixes with the added alumina nanofibers. Differential scanning calorimeter shows changes in melting and crystallization point and degree of crystallinity for 1wt.% nanocomposites. The result also indicated that alumina nanofiber serves as nucleating agents in PEEK nanocomposites. The X-ray diffractogram data indicated that the crystallinity of the PEEK nanocomposites was highest for 1wt.% alumina nanofiber. The thermogravimetry analysis, shows that thermal stability for alumina nanofiber/PEEK nano-composites was enhanced compared to that of the pure PEEK.